Boyle’s Reductive Occasionalism - Daniel Layman (Journal of Modern Philosophy)
Was Robert Boyle an occasionalist? And if so, what kind of occasionalist was he? These questions have long troubled commentators, as Boyle’s texts often seem to offer both endorsements of occasionalism and affirmations of bodies’ causal powers. I argue that Boyle’s position is best understood as reductive occasionalism, according to which (a) bodily powers are relations between bodies and God’s action in the world, and (b) there is no causal efficacy in bodies that is not strictly identical to God’s nomological causal efficacy.